Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian: (Survei pada konsumen Lawang Coffee di Kecamatan Leuwisari Kabupaten Tasikmalaya) - Gilang Permana; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and analyze the effect of product quality and promotion on purchasing decisions (a survey of Lawang Coffee consumers in Leuwisari, Tasikmalaya), both partially and simultaneously. The method used in this research is descriptive analysis method with a causal quantitative survey approach. The population studied were 100 respondents. The data collected in the form of secondary and primary data. Data analysis in this study using Multiple Regression Analysis using SPSS software version 25. The results of this study indicate that product quality and promotion simultaneously affect purchasing decisions at Lawang Coffee in Leuwisari District. Product quality partially influences purchasing decisions at Lawang Coffee in Leuwisari District. Promotion partially affects purchasing decisions at Lawang Coffee in Leuwisari District.